Effect of Multiple Intelligences’ Teaching on Academic Achievement of High Achievers in Science at Elementary Level - EdIram Naz (JSE, 2023)
Every human being has different types of intelligences. Through the usage of multiple intelligences theory, individuals may be encouraged to use their preferred intelligences in their own learning area, and instructional activities may be appealed to different forms of intelligences. Teachers are using multiple intelligences of students to increase their learning. The main aim of the study was to find the effect of multiple intelligences’ based teaching on academic achievement of high achievers in science at elementary level. T